VIOLATION OF PATIENT’S LEGAL RIGHTS IN AESTHETIC BEAUTY CLINIC - Siska Diana Sari (Legal Standing : Jurnal Ilmu Hukum, 2020)
Beauty Clinic is an outpatient health care facility that provides medical services(consultation, examination, treatment, and medical action) to overcome variousconditions / diseases which relate to person's beauty (aesthetic appearance) that is performed by medical personnel (doctors, dentists, medical specialist, and dentalspecialist) based on their expertise and authority.  However, behind the rapid growth of beauty clinics, there are several negative sides and one of them is when the consumer has already paid costly for beauty products services and beauty services,  the consumer experiences complications in its use which actually worsens the condition of consumer's skin. Moreover, it needs efforts from authorized stakeholders in order to protect legal rights for aesthetic beauty clinic patients. Various methods and motives of violations which are committed lead to mere profit. Furthermore, the research method that was used in this research was legalsocial (non-doctrinal) research method by an interactional (micro) approach with qualitative analysis or qualitative methods.